A case of gallbladder cancer combined with ectopic individual opening of pancreatic and bile ducts to the duodenal bulb - Lee, Woohyung (Korean J Hepatobiliary Pancreat Surg, 2015)
Ectopic opening of the pancreatic and bile ducts (EOPBD) into the duodenal bulb is an extremely rare congenital anomaly with unknown clinical implications. We presented a case of gallbladder cancer with EOPBD into the duodenal bulb. A 57-year-old male was referred to our hospital with intermittent right upper abdominal pain. Endoscopic retrograde cholangiopancreatography and magnetic resonance cholangiopancreatography showed individual EOPBD into the duodenal bulb with no papillary structure, and a focal nodular lesion in the gallbladder. A follow-up abdominal computed tomography scan 9 months later revealed a slight increase in the size of the fundal nodule, which was suspected as gallbladder cancer. An intraoperative frozen biopsy identified the nodular lesion as adenocarcinoma involving the cystic duct, and the patient underwent radical cholecystectomy including bile duct resection with hepaticojejunostomy. EOPBD is an extremely rare condition that can be associated with gallbladder malignancy as well as benign disease. Clinicians should follow up carefully and consider surgical treatment for suspected malignant lesions.